Constraints of Fe isotopes on the origin of volcanic-hosted Fe-oxide deposits: A case study of the Late Cambrian 7918 Fe deposit, North Altun orogenic belt, Xinjiang, NW China. (1st June 2021) - Meng, Lingtong; Chen, Bailin; Wu, Yu; Wang, Yong
Graphical abstract: Highlights: The 7918 iron deposit is hydrothermal in origin. Volcanic rocks hosting orebodies act as a main Fe source in the 7918 deposit. A three-stage model has been proposed to account for genesis of 7918 iron deposit. Abstract: The 7918 Fe deposit in the North Altun orogenic belt, NW China, is composed of strata-bound orebodies between Late Cambrian basalts and marble, associated with intensive skarn-type alteration. Basalts close to the orebodies are altered, with gradational contacts to skarns. Variations of major and trace elements and δ 57 Fe values of low-Ti and high-Ti basalts reflect the role of both magmatic evolution and hydrothermal alteration. Negative correlations between δ 57 Fe and TFeO/TiO2 and between Na2 O and TFeO/TiO2 of high-Ti basalts are explained by lighter Fe isotopes leached from basalts during water–rock reaction. Hence, we considered basalts as the main source of Fe. Magnetite precipitation was related to a retrograde skarn stage. Early-precipitated magnetite has lower incompatible trace elements (Lu, Zr, Hf, Nb, Ta, and Yb), higher compatible trace elements (Co and Ni), and lower δ 57 Fe values than late-precipitated magnetite. Hydrothermal fluids equilibrated with early-precipitated magnetite (−0.11‰ to 0.16‰) and late-precipitated magnetite (0.22‰ to 0.27‰) have δ 57 Fe values of −0.38‰ to −0.11‰ and −0.05‰ to 0.00‰, respectively. The isotopically heavier late-phase fluids indicate an increase of oxygen fugacity, in which Fe 2+ was mostly oxidized to Fe 3+ . This is also consistent with reduced V concentrations from early-precipitated to late-precipitated magnetite. Our new data and previous geochronological results suggested that the 7918 Fe deposit records a continuous process of volcanic eruption, hydrothermal alteration, and Fe mineralization, which was related to a deep "magma chamber" formed at a subduction-related setting.